Evolution of the multi-domain structures of virulence genes in the human malaria parasite, Plasmodium falciparum - Buckee, C; Recker, M (Public Library of Science, 2012)
The var gene family of Plasmodium falciparum encodes the immunodominant variant surface antigens PfEMP1. These highly polymorphic proteins are important virulence factors that mediate cytoadhesion to a variety of host tissues, causing sequestration of parasitized red blood cells in vital organs, including the brain or placenta. Acquisition of variant-specific antibodies correlates with protection against severe malarial infections; however, understanding the relationship between gene expression and infection outcome is complicated by the modular genetic architectures of var genes that encode varying numbers of antigenic domains with differential binding specificities. By analyzing the domain architectures of fully sequenced var gene repertoires we reveal a significant, non-random association between the number of domains comprising a var gene and their sequence conservation. As such, var genes can be grouped into those that are short and diverse and genes that are long and conserved, suggesting gene length as an important characteristic in the classification of var genes. We then use an evolutionary framework to demonstrate how the same evolutionary forces acting on the level of an individual gene may have also shaped the parasite's gene repertoire. The observed associations between sequence conservation, gene architecture and repertoire structure can thus be explained by a trade-off between optimizing within-host fitness and minimizing between-host immune selection pressure. Our results demonstrate how simple evolutionary mechanisms can explain var gene structuring on multiple levels and have important implications for understanding the multifaceted epidemiology of P. falciparum malaria.